2022
DOI: 10.3390/drones6070162
|View full text |Cite
|
Sign up to set email alerts
|

SR-DeblurUGAN: An End-to-End Super-Resolution and Deblurring Model with High Performance

Abstract: In this paper, we consider the difference in the abstraction level of features extracted by different perceptual layers and use a weighted perceptual loss-based generative adversarial network to deblur the UAV images, which removes the blur and restores the texture details of the images well. The perceptual loss is used as an objective evaluation index for training process monitoring and model selection, which eliminates the need for extensive manual comparison of the deblurring effect and facilitates model se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Correspondingly, WRA-Net-Wide Receptive Field Attention Network, see [92]-was introduced to deblur the motion-blurred images, which improved the crop weed segmentation accuracy. Moreover, Xiao et al [93] introduced a novel hybrid technique, namely SR-DeblurUGAN, encompassing both image deblurring and super-resolution, which gained a stable performance on agricultural drone image enhancement.…”
Section: Deep Neural Network and Generative Adversarial Networkmentioning
confidence: 99%
“…Correspondingly, WRA-Net-Wide Receptive Field Attention Network, see [92]-was introduced to deblur the motion-blurred images, which improved the crop weed segmentation accuracy. Moreover, Xiao et al [93] introduced a novel hybrid technique, namely SR-DeblurUGAN, encompassing both image deblurring and super-resolution, which gained a stable performance on agricultural drone image enhancement.…”
Section: Deep Neural Network and Generative Adversarial Networkmentioning
confidence: 99%
“…The UNET model has shown outstanding performance in image segmentation tasks, particularly in tasks requiring precise detail segmentation. In recent years, experts have attempted to introduce it into the field of image super-resolution with good results [35][36][37][38]. The traditional UNET architecture efficiently extracts multi-scale features through design, consisting of symmetric branches for encoding and decoding.…”
Section: Structure Of the Modelmentioning
confidence: 99%
“…The smooth l_1 loss is also utilized in this process. In contrast, Xiao et al [34] proposed a two-stage image quality improvement model that first employs super-resolution using SRGAN, followed by correction and deblurring using a UNet-GAN model. Similarly, Li et al [35] suggested a super-resolution model based on a GAN to improve UAV detection.…”
Section: Related Workmentioning
confidence: 99%